Self-Storage Investment Case in Kentucky. Issue 2 (1st January 2016) - Simons, Robert A.; Helm, Mark
Abstract : This is an investment case study. The investment vehicle is an existing self-storage (SS) business. You have been offered partnership shares in an ongoing SS business that has just been purchased. You desire a reasonable risk-adjusted rate of return, but you do not want any recourse beyond your original investment. To what extent do the facts of the case and partnership agreement encourage or discourage investment in the legal entity poised to purchase this self-storage property?